Mathematics Emerging: From Colorado to Oxford. Issue 5 (28th May 2019) - Anderson, Marlow; Hollings, Christopher; Wilson, Robin
Abstract: History of mathematics courses based on original source materials are becoming increasingly common. However, are they more suitable for particular types of students? Here we compare two such upper-level courses, with a similar structure and using the same textbook, taken by liberal arts students at Colorado College and mathematics specialists at Oxford University.